The Comparison of Managerial Performance of Major Cities in the World a Case Study of Tehran City - Mirzaee Yaser, Mirzaee Ehsan, Zahra Hosseinkhani (International Journal of Modern Agriculture, 2021)
Cities represent the driving force of development in economic, social, and cultural life, reflecting also the spatial organization of human society. Taking into account the fact that cities are becoming generators of economic development and a source of growth for the national economy, there is an increasing urge to identify the stages of development and to establish a system for the ranking and positioning of cities and regions in this process (the level of categorization). This will allow the preparation of appropriate strategic and development guidelines for cities and urban regions to take place